ASSESSING THE EFFECTIVENESS OF INTERPROFESSIONAL COLLABORATION BETWEEN NURSING SPECIALISTS AND MIDWIFERY TECHNICIANS IN IMPROVING MATERNAL AND CHILD HEALTH: Keywords: interprofessional collaboration, nursing specialists, midwifery technicians, maternal health, child health, Saudi Arabia - Mayam Naif Oudah Aljameeli, Shroug khalaf Mutilk Alorayfij, Faizah Hammad Salman Aljameli, Rahima Awad Ashaban Al-Anazi, Seham Khaled Suleiman Al Majdi, Ghadah Abdulaziz AAlkhaluf (Chelonian Research Foundation, 2022)
Interprofessional collaboration between nursing specialists and midwifery technicians is crucial for improving maternal and child health outcomes. This study aims to assess the effectiveness of collaboration between these healthcare professionals in Hafer Albatin hospitals, Saudi Arabia. A mixed-methods approach was employed, involving a survey of 150 nursing specialists and midwifery technicians and semi-structured interviews with 20 healthcare professionals and 30 patients. The survey assessed perceptions of collaboration, job satisfaction, and patient outcomes, while the interviews explored experiences and challenges related to interprofessional collaboration. The findings revealed that effective collaboration between nursing specialists and midwifery technicians was associated with improved patient outcomes, increased job satisfaction, and enhanced quality of care. However, challenges such as communication barriers, role ambiguity, and hierarchical structures were identified as obstacles to effective collaboration. The study highlights the need for interventions to foster interprofessional collaboration, including communication skills training, role clarification, and supportive organizational policies.